Circulating Tumor Cells: A Review of Non–EpCAM-Based Approaches for Cell Enrichment and Isolation. (6th January 2020) - Gabriel, Marta Tellez; Calleja, Lidia Rodriguez; Chalopin, Antoine; Ory, Benjamin; Heymann, Dominique
Abstract: BACKGROUND: Circulating tumor cells (CTCs) are biomarkers for noninvasively measuring the evolution of tumor genotypes during treatment and disease progression. Recent technical progress has made it possible to detect and characterize CTCs at the single-cell level in blood. CONTENT: Most current methods are based on epithelial cell adhesion molecule (EpCAM) detection, but numerous studies have demonstrated that EpCAM is not a universal marker for CTC detection because it fails to detect both carcinoma cells that undergo epithelial-mesenchymal transition (EMT) and CTCs of mesenchymal origin. Moreover, EpCAM expression has been found in patients with benign diseases. A large proportion of the current studies and reviews about CTCs describe EpCAM-based methods, but there is evidence that not all tumor cells can be detected using this marker. Here we describe the most recent EpCAM-independent methods for enriching, isolating, and characterizing CTCs on the basis of physical and biological characteristics and point out the main advantages and disadvantages of these methods. SUMMARY: CTCs offer an opportunity to obtain key biological information required for the development of personalized medicine. However, there is no universal marker of these cells. To strengthen the clinical utility of CTCs, it is important to improve existing technologies and develop new, non–EpCAM-based systems to enrich and isolate CTCs.